Simultaneous 18-FDG PET and MR imaging in lower extremity arterial disease - Koppara, Tobias; Dregely, Isabel; Nekolla, Stephan G.; Nährig, Jörg; Langwieser, Nicolas; Bradaric, Christian; Ganter, Carl; Laugwitz, Karl-Ludwig; Schwaiger, Markus; Ibrahim, Tareq (Frontiers in Cardiovascular Medicine, 2024)
Background Simultaneous positron emission tomography (PET) and magnetic resonance imaging (MRI) is a novel hybrid imaging method integrating the advances of morphological tissue characterization of MRI with the pathophysiological insights of PET applications. Aim This study evaluated the use of simultaneous 18-FDG PET/MR imaging for characterizing atherosclerotic lesions in lower extremity arterial disease (LEAD). Methods Eight patients with symptomatic stenoses of the superficial femoral artery (SFA) under simultaneous acquisition of 18-FDG PET and contrast-enhanced MRI using an integrated whole-body PET/MRI scanner. Invasive plaque characterization of the SFA was performed by intravascular imaging using optical coherence tomography. Histological analysis of plaque specimens was performed after directional atherectomy. Results MRI showed contrast enhancement at the site of arterial stenosis, as assessed on T2-w and T1-w images, compared to a control area of the contralateral SFA (0.38 ± 0.15 cm vs. 0.23 ± 0.11 cm; 1.77 ± 0.19 vs. 1.57 ± 0.15; p-value <0.05). On PET imaging, uptake of 18F-FDG (target-to-background ratio TBR > 1) at the level of symptomatic stenosis was observed in all but one patient. Contrast medium-induced MR signal enhancement was detected in all plaques, whereas FDG uptake in PET imaging was increased in lesions with active fibroatheroma and reduced in fibrocalcified lesions. Conclusion In this multimodal imaging study, we report the feasibility and challenges of simultaneous PET/MR imaging of LEAD, which might offer new perspectives for risk estimation.